#TITLE_ALTERNATIVE# - SAFITRI (NIM: 25112013); pembimbing: Dr. Akhmad Riqqi, ST.,M.Si ; Dr. Albertus Deliar, ST., SITARANI
The main objective of the research is to see how LADM and 3D cadastre concept can be implemented in cadastral data management for various purposes in Indonesia. Multipurpose cadastre capable of supporting all primary functions in land administration, i.e land tenure, land value, landuse, and land development. These land administration fucntions in Indonesia are still managed separately. The integration among land administration functions can be accommodated by spatial data infrastructure (SDI). SDI comprises standard, data, access network, policies, and people, that support data sharing among different institutions to achieve sustainable development. Indonesia has already had 2D cadastral system, however this system is not appropriate anymore. 3D cadastral system is needed because of land dynamic, as the result of population growth, which increase vertical development. Thus, multipurpose cadastre should accommodate data sharing and 3D cadastre concept. LADM is an international standard for land information domain, which support data sharing and 3D cadastre concept. The methodology of this research is divided into two main parts. The first part is to analyze the requirements of cadastral data management using SDI approach. This process is supported by reviewing literatures related to 3D cadastre in Indonesia. The second one is to develop the conceptual architecture of cadastral data management based on LADM with Country Profile of Indonesia. The development of 2D and 3D geometries of parcels and building is also a part of this process. To support data sharing of 3D spatial data, Nomor Identifikasi Bidang (NIB) is needed as a common unique identity that can be used to create linkage among cadastral data in various institutions. Therefore, the development of NIB for property (3D) becomes a part of this process. The implementation of conceptual design is verified by simulation and assessment questions. The result of this research is the conceptual architecture of multipurpose cadastre, which is expected to be a standard for 3D cadastral data management in Indonesia.